THE IMPLEMENTATION OF MEDIATION IN THE RESOLUTION OF INTERNATIONAL TRADE DISPUTES - Ruwaidah Afiyati (UNISSULA, 2022)
The purpose of this paper is to find out mediation in the settlement of disputes or international trade disputes by Business Actors, and the role of the ITPC in the event of a dispute between the parties involved in international trade transactions. This research used a normative juridical approach. The research results state that settlement of international trade disputes, in its implementation, business people prefer the mediation route, because of the benefits or advantages that business people get when using the mediation route. Among other things, the parties requested or appointed by the parties are neutral parties, procedures are fast, informal, time and cost efficient, confidentiality is maintained, prioritizes maintaining a sustainable working relationship in business as well as settlement decisions determined and agreed upon by the parties to create peace.